Reproductive Coercion: Baby, If You Love Me... Issue 4 (July 2018) - Kovar, Cheryl L.
Abstract : Abstract: Background and Purpose: Reproductive coercion involves behavior that interferes with the individual's unique ability to make decisions about their reproductive health. The concept was first recognized in 2010. Reproductive coercion is intended to maintain power and control in a relationship by someone past, present, or future wishing to be involved in an intimate or dating relationship with an adult or adolescent. Three forms of coercion have been identified: contraceptive sabotage, pregnancy pressure, and control of pregnancy outcomes. Methods: A search for scientific literature was conducted examining studies involving reproductive coercion as well as evidence-based interventions that could be used by nurses in the clinic setting. Conclusions: Prevalence of reproductive coercion is estimated to range from 8% to 16%. There is a high association between intimate partner violence (IPV), sexually transmitted infections (STIs), and unintended pregnancy. Adolescents are at greater risk for reproductive coercion than older women. Implications for Practice: There are interventions we can incorporate into our clinical practices to screen and assess women for reproductive coercion. Women experiencing reproductive coercion are at risk for unintended pregnancy, STIs, IPV, and forced pregnancy outcomes. Abstract : Reproductive coercion involves behavior that purposely interferes with a woman's decision-making about reproductive health and includes contraceptive sabotage, pregnancy pressure, and control of pregnancy outcomes. Reproductive coercion has been associated with increased risks of intimate partner violence, sexually transmitted infections, unintended pregnancy, and forced pregnancy outcomes. Review of the clinical implications of reproductive coercion is presented.